ANTHROPOGENIC POLLUTION IN MARACAIBO LAKE, VENEZUELA (Biocenosis, 2013)
The contamination of Lake Maracaibo Basin is directly linked to human activities, among which the discharge of wastewater from domestic and industrial, especially the petrochemical industry. This environmental problem has created an ecological imbalance of biotic and abiotic components of the largest estuary in the American continent and the most important in the western Venezuela part, in biological, socioeconomical and political viewpoint, because of its natural riches and geographical location. This review provides a comprehensive view on the environmental impact in the System of Maracaibo, on the bodies of water, biota and fishing.
Keywords: Marine pollution; System of Maracaibo; Effluents; Contaminants; Heavy metals; Estuary